2018
DOI: 10.3164/jcbn.17-68
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic property of soy isoflavones from hypocotyl in Goto-Kakizaki diabetic rats

Abstract: The present study was carried out to investigate the hypoglycemic effect of soy isoflavones from hypocotyl in GK diabetic rats. A single administration and long-term administration tests were conducted in GK diabetic rats to test the hypoglycemic effect of soy isoflavones. At the end of long-term administration trial, blood protein, cholesterol, triglyceride, glycosylated serum protein, C-reactive protein, insulin, aminotransferase, lipid peroxide, interleukin-6, tumor necrosis factor-α were estimated. Inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Furthermore, it is logic to find the downregulation of CRP level together with reduced TNF- α and IL-2 where CRP is produced by hepatic cells in response to such cytokines [97]. The decrement in CRP after soy isoflavone treatment was in harmony with results of Fanti et al [98] and Jin et al [99].…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, it is logic to find the downregulation of CRP level together with reduced TNF- α and IL-2 where CRP is produced by hepatic cells in response to such cytokines [97]. The decrement in CRP after soy isoflavone treatment was in harmony with results of Fanti et al [98] and Jin et al [99].…”
Section: Discussionmentioning
confidence: 59%
“…(45,46) Some authors showed that chronic soy ISO even from hypocotyl can decrease lipid perioxidation and some pro inflammatory cytokines markers. (29) The efficiency of TBARS inhibition may depend on the individual isoflavones concentration in the extract, with some compounds having low or moderate efficiency to inhibit TBARS, (46) which may explain the slight interaction observed in this study (p = 0.037), and also why other studies found no changes in lipid peroxidation markers with ISO. (32,33) One of the main benefits from exercise training is related to improvements in antioxidant defense.…”
Section: Discussionmentioning
confidence: 61%
“…In some studies, there was a decrease in ROS production, and an increase in SOD in postmenopausal women, (26,27) other showed that genistein, a soy isoflavone, or the soy isoflavone from hypocotyl could decrease oxidative stress via lowering lipid peroxidation, and improving antioxidant enzymes. (28,29) Besides, other studies find that a high isoflavone consumption, as well as exercise, is effective in increasing nitrite concentrations and improving endothelial function. (30,31) However, there are also studies that did not report any effect in oxidative markers with ISO.…”
mentioning
confidence: 99%
“…(9)(10)(11)(12)(13) Soy isoflavones, such as daidzein, glycitein, and genistein, (14) are a group of compounds present in soybean and function as potent antioxidants. (15,16) Jin et al (17) reported the effect of soy isoflavones, including daidzein (61.7%), glycitein (21.5%) and genistein (16.2%), on diabetic rats. They showed that an improvement in postprandial blood glucose levels and a significant suppression of blood lipid peroxide can be achieved by single or long-term administration of soy isoflavones, respectively.…”
mentioning
confidence: 99%
“…They showed that an improvement in postprandial blood glucose levels and a significant suppression of blood lipid peroxide can be achieved by single or long-term administration of soy isoflavones, respectively. (17) Additionally, soy isoflavones act as phytoestrogens and interact with animal and human estrogen receptors and produce non-hormonal effects. (18)(19)(20)(21)(22)(23)(24) We found that daidzein and glycitein inhibited influenza virus replication and suggested that the regulation by daidzein is not directly associated with viral enzymes but rather with host-cellular metabolism (unpublished data).…”
mentioning
confidence: 99%